Characterization of protein lactylation in healthy and ischemic mouse hearts - Wu, Daiqian; Tang, Yuanjuan; Li, Xingbing; Xiong, Shiqiang; Zhang, Zhen; Fu, Jinjuan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundRecent findings highlight the growing importance of protein lactylation, a modification driven by lactate, in healthy and diseased states. However, its significance in myocardial infarction (MI) remains unclear. Here, we characterized lactylation in healthy and ischemic hearts, revealing its profound implications.MethodsGlobal proteomics and lactylome profiling were conducted on the hearts of healthy mice and mice with induced MI. Protein expression analysis, enrichment analysis, cellular compartment analysis, and protein-protein interaction network construction were conducted to identify potential molecular features. The changes in total protein lactylation levels and the lactylation levels of identified representative proteins in healthy and ischemic hearts were validated.ResultsProteomic analysis revealed that MI led to a metabolic shift from oxidative phosphorylation and fatty acid β-oxidation toward hypoxia-induced glycolysis. Western blotting and immunofluorescence analyses conclusively demonstrated the presence of protein lactylation in healthy hearts, with significantly elevated lactylation levels following MI. Lactylome profiling identified 1,674 lactylation sites across 477 cardiac proteins under physiological conditions, with 44.03% (210/477) being singly-lactylated proteins. Myosin-6 and titin were identified as the proteins having the most lactylation sites in the heart. Comparative analysis revealed 61 upregulated lactylation sites across 53 proteins and 30 downregulated sites across 27 proteins in infarcted hearts relative to healthy controls. Functional enrichment analyses suggested that proteins with altered lactylation modification post-MI mainly included metabolic enzymes, cytoskeletal proteins, and RNA binding proteins. We created lactylation modification maps for these three types of proteins in ischemic hearts.ConclusionsWe present the first comprehensive lactylation atlas in healthy and ischemic mouse hearts, offering new avenues to explore MI and cardiovascular diseases.